Efektifitas Pemberdayaan dalam Mengembangkan Pariwisata Berkelanjutan Pokdarwis Desa Ardy Mulyo Kalimantan Utara - Yani, Indah; Larasati, Dini (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2023)
This study aims to analyze community empowerment and measure the effectiveness of Pokdarwis in developing sustainable tourism. This research is a descriptive research with a qualitative approach. The results of this study indicate that the stages of community empowerment have not been carried out optimally, as seen from the level of community involvement in tourism development. However, from an organizational aspect, Pokdarwis Ardy Mulyo has been able to initiate and create innovations in tourism management. The level of community empowerment shows that the economic and political aspects have not been fully developed, while the psychological and social aspects are still a challenge. The effectiveness of Pokdarwis in empowering communities in sustainable tourism development is quite good, but there are still obstacles in increasing community involvement in tourism development. The Tourism and Culture Office of Bulungan Regency must empower the community through training and mentoring, in accordance with the potential of natural and cultural resources in Ardy Mulyo Village. The Ardy Mulyo Village Government can utilize websites and online services for the promotion of tourism villages. Pokdarwis Ardy Mulyo must be willing to work with various stakeholders, and Ardy Mulyo residents must create an environment that reflects their village as a tourist destination.